Mekanisme Panopticism dan Resistensi Masyarakat terhadap Sistem Pengobatan Modern: Studi tentang Reaksi atas Praktik Relasi Kuasa dalam Dunia Medis - Septi Ariadi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Panopticism in the medical world reflects a structural dominance of power. Panopticism takes the form of medical regime authority aimed at surveillance, regulation, and discipline to frame the thoughts and actions of individuals in line with modern health standards. The issue is that panopticism doesn't always work effectively according to the desires of the medical regime. Therefore, this study aims to analyze the mechanisms of panopticism and identify the spectrum of resistance to the modern healthcare system. Using an applied method, the study found resistance in modern health practices, namely: (a) accessing modern treatment but accompanied by skepticism and criticism of modern medicine; (b) developing a pluralistic or combinative medical orientation; (c) opting out and constructing alternative discourses about the healthcare system following autonomy of will and power. Health resistance is triggered by skepticism and distrust, asymmetrical relations based on scientific authority, limited access to modern medical products, and the existence of informal networks, as well as the strong role of local social and cultural figures in directing the choices of healthcare systems for the community.